Use of Soil Infiltration Capacity and Stream Flow Velocity to Estimate Physical Flood Vulnerability under Land-Use Change Scenarios (2023)
Land-use changes produce variations in upper soil hydraulic properties and alter the hydrological response and hydraulic behavior of streams. Thus, the combined effect of variations in soil properties and current hydraulics interacts with the exposure of structures exposed and their degree of physical vulnerability. This study aims to evaluate the effect of land-use evolution from 1976 to 2017 on the physical vulnerability of structures exposed to floods in the Combeima cathment, Colombia, proposing two novel approaches: (i) based on soil infiltration capacity variation (CN) in the basin and changes in stream flow velocity (v), (ii) through soil water storage variation in the root zone (Hu). Hydrological and hydraulic modeling and the implementation of four physical vulnerability assessment methods were performed using GIS analysis. Findings indicate that simplifying physical vulnerability estimations through CN, Hu, and (Formula presented.) variations in catchments and at cross-section resolutions is possible, allowing a detailed analysis of the land-use change effect on the vulnerability of structures. The scaling behavior of the physical vulnerability of structures was identified when Hu is defined as a scale variable and, similarly, concerning flow velocity in the stream. Therefore, applying the power law could be useful in planning processes with limited information.